Employees Work Motivation and Its Effect on their Performance - Chethan Kumar M. J. (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
Working condition denotes all the organisation inputs which aim at the employees satisfactions among enhancing organisation effectiveness. The basic purpose is to develop jobs and working conditions that are excellent for employees as well as the health of the organisation. It refers to level of satisfaction through working condition and employee relation as well as labour’s relation. This study is focus on to understand the working condition, labour relation in different sectors. For the purpose of the study data has been collected from both primary and secondary source. Primary data has been collected from labour class who have working at different companies. Secondary data has been collected from journals, books and internet. Collected data has been analysed, interpreted and conclusion is drawn at the end.